2017
DOI: 10.1002/ijc.30558
|View full text |Cite
|
Sign up to set email alerts
|

Detection of colorectal neoplasia: Combination of eight blood-based, cancer-associated protein biomarkers

Abstract: Serological biomarkers may be an option for early detection of colorectal cancer (CRC). The present study assessed eight cancer-associated protein biomarkers in plasma from subjects undergoing first time ever colonoscopy due to symptoms attributable to colorectal neoplasia. Plasma AFP, CA19-9, CEA, hs-CRP, CyFra21-1, Ferritin, Galectin-3 and TIMP-1 were determined in EDTA-plasma using the Abbott ARCHITECT® automated immunoassay platform. Primary endpoints were detection of (i) CRC and high-risk adenoma and (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 51 publications
(111 reference statements)
1
52
0
1
Order By: Relevance
“…By focusing on CRC risk stratification within symptomatic patients, the expectation is that the colonoscopy compliance of patients with the apparent highest need can be increased. Other groups [11, 13] have also approached the development of tests for symptomatic patients, though none have yet validated their tests and the tests’ proposed uses have varied. Our view is that CRC tests for symptomatic patients are most helpful when directed to patients who resist colonoscopies despite the presence of symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By focusing on CRC risk stratification within symptomatic patients, the expectation is that the colonoscopy compliance of patients with the apparent highest need can be increased. Other groups [11, 13] have also approached the development of tests for symptomatic patients, though none have yet validated their tests and the tests’ proposed uses have varied. Our view is that CRC tests for symptomatic patients are most helpful when directed to patients who resist colonoscopies despite the presence of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Given the attractiveness of a low-burden CRC test for symptomatic patients, several groups have focused efforts here [10, 11, 13, 14]. The highest performing test, and the only validated test to date, was a blood-based test developed earlier in our laboratory [10, 14] using a sample set mirroring the composition of the intent-to-test (ITT) symptomatic population [14].…”
Section: Introductionmentioning
confidence: 99%
“…It will also be important to seek its combination partners because it has become evident that the usage of multiple biomarkers show preferable results when used in CRC diagnosis. 16,17) Furthermore, considering that only a small portion of human serum is currently available for routine CRC screening, improvement of Ct-OATP1B3 mRNA detection method is necessary. For example, development of a pre-amplification of EV mRNA or a more sensitive quantification method.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the AUC of the combination of these markers was greater than that of each tumor marker detected individually for both GC and CRC, which suggested that the combined detection of these four tumor markers may prove to be useful for the diagnosis of GC and CRC [ 20 ]. Wilhelmsen M et al found that a combination of all 8 serological protein biomarkers, including alpha fetoprotein (AFP), CA19-9, CEA, high-sensitivity C-reaction protein (hs-CRP), CyFra21-1, ferritin, galectin-3 and tissue inhibitor of metalloproteinases-1 (TIMP-1), provided a significant improvement for the identification of subjects with a high risk of CRC [ 21 ]. Werner S et al tested serum samples from 1660 blood samples from participants in a colonoscopy screening with a 5-marker blood test (CEA, anti-p53, osteopontin, seprase and ferritin) and found that the diagnostic performance for CRC of the 5-marker test was comparable with that of the guaiac-based fecal occult blood test (gFOBT), as they both identify 39% of all CRC cases at the specificity of 96% [ 22 ].…”
Section: Discussionmentioning
confidence: 99%